The Oxford handbook of theology and modern European thought - Adams, Nicholas (Oxford handbooks in religion and theology, 2013)
This title describes a wide range of philosophies, cultural programmes, and political arguments developed in Europe in the period following the French Revolution. This handbook charts and explores recurring themes and approaches to this broad and complex topic, particularly with regard to theology.